PENGARUH LATIHAN GERAK DASAR DAN LATIHAN PERNAFASAN MERPATI PUTIH TERHADAP PENINGKATAN KEBUGARAN JASMANI ANGGOTA UKM PENCAK SILAT MERPATI PUTIH UNIVERSITAS NEGERI MALANG - Santoso, Arif Teguh; Mardianto, Mardianto; Supriyadi, Supriyadi (Jurnal Sport Science, 2016)
ABSTRACT :The purpose of this study was to determine: 1) The effect of basic movement with breathing exercises and basic motion martial arts merpati putih influence the improvement of physical fitness, 2) The effect ofÂ basic movement exercises martial arts merpati putih influence the improvement of physical fitness, 3) The differences in effects of exercise basic movements with breathing and movement exercises basic martial arts merpati putih influence the improvement of physical fitness. This type of research is pre experimental study with using matching only design. The subjects were members UKM Martial Arts Merpati Putih active totaling 24 people.Based on test Anova using one way anova obtained, the basic movement and breathing p = 0.000 < 0.05 and p basic movement = 0.000 p < 0.05.Â From these results indicate p <0.05 which means that Ho refused. So we can conclude 1) Basic movement exercises and breathing exercises martial arts merpati putih influence the improvement of physical fitness, 2) Basic movement exercises martial arts merpati putih influence the improvement of physical fitness, 3) The differences between the influence of basic movement exercises with breathing and basic motion Martial Arts Merpati Putih the improvement of physical fitness. Further research needs to be held with the hope that will provide wider experimental results.Keywords :Basic Motion Exercises, Exercises Respiratory, Merpati Putih, Physical Fitness